Functional traits illuminate the selective impacts of different fishing gears on coral reefs. Issue 2 (26th December 2019) - Mbaru, Emmanuel K.; Graham, Nicholas A. J.; McClanahan, Timothy R.; Cinner, Joshua E.
Abstract: Unsustainable fishing is a major driver of change in marine ecosystems. The ways that fishing gears target fishes with different ecological functions are unclear, particularly in complex multispecies fisheries. Here, we examine whether artisanal fishing gears selectively target fishes with unique combinations of ecological traits (diet, body size, depth, position in water column, period of activity, schooling behaviour) in a coral reef ecosystem. We use coral reef fish landing data from 25 sites along the Kenyan coast collected over a 7‐year period. All fishing gears targeted a wide diversity of traits, but with some differentiation among gears. Fish assemblages captured by spearguns were significantly different from the other gear types, specializing on diurnal species that feed on sessile invertivores. Nets, including gillnets and beachseines, targeted the most functional diversity. Escape slot traps targeted the least functionally diverse assemblages. Basket traps and escape slot traps targeted the most functionally similar species of all two‐gear combinations. There were 163 functional entities (unique combinations of traits) captured in the fishery; however, 50% of the catch by each gear was from only two to six functional entities. Most of the differences in gear selectivity were due to unique and rarely targeted functional entities, that made up only a small proportion of the catch. Synthesis and applications . Coral reef fisheries target a breadth of functional entities (unique combinations of traits), but catches are heavily skewed towards relatively few functional entities. While banning specific gears will benefit rare functional entities in the catch, effort reductions will be necessary to alleviate pressure on commonly targeted functional entities. Abstract : Coral reef fisheries target a breadth of functional entities (unique combinations of traits), but catches are heavily skewed towards relatively few functional entities. While banning specific gears will benefit rare functional entities in the catch, effort reductions will be necessary to alleviate pressure on commonly targeted functional entities.